Conventional versus automatic weather station evaluated differences with statistical indixes Chapingo, Mexico - Arteaga-Ramírez, Ramón; Cervantes-Osornio, Rocio; Vázquez Peña, Mario Alberto; Ojeda Bustamante, Waldo (Revista Mexicana de Ciencias Agrícolas, 2017)
The objective of this research was to compare the meteorological data measured by a conventional station against the same but obtained by an automatic one, both stations are located at Universidad Autónoma Chapingo, these data were: maximum temperature, minimum, maximum relative humidity and mínimum, theses were collected on a daily basis and analyzed graphically and statistically, by means of the inconsistency and consistency coefficient, the square root of the mean square error and normalized, the concordance index or Willmott, the determination coefficient, a regression analysis, systematic error and random error, of the period from January 2004 to June, 2013. It was found that for the variables maximum temperature and minimum temperature, the data of the automatic meteorological station or those of the conventional one can be used without distinction since the data are similar.